The Effect Of Giant Snakes And Ladders Game On Changes In The Development Of Cognitive Abilities Of Children Aged 5-6 Years At Cut Nyak Dhien Kindergarten In Malang City. - Mira Diadhita Prameswari; Rifzul Maulina; Reny Retnaningsih (Universitas Muhammadiyah Malang, 2025)
Background : Cognitive abilities represent a fundamental component of mental functions, encompassing processes such as perception, thinking, memory, and information processing. These cognitive functions are essential in facilitating individuals to acquire knowledge, address challenges, and formulate future plans. Data from UNICEF (2022) reveals that children aged 36–59 months across the globe continue to face challenges in their cognitive development. In Indonesia, about 7.51% of children under the age of five exhibit signs of developmental delays. Additionally, the Central Statistics Agency (BPS) reported in 2020 that approximately 60% of preschool-aged children in the country experience issues related to cognitive development. One effective and enjoyable approach to stimulate cognitive growth in early childhood is through the use of educational games. Among these, the giant snakes and ladders game has been recognized for its potential to enhance cognitive functioning in young children. Research Methods : This research utilized a pre-experimental method with a one-group pretest-posttest design. Participants were selected through purposive sampling based on predetermined criteria. Data collection was carried out using structured observation sheets, and the results were analyzed through a paired sample t-test. The findings revealed a 2-tailed significance value of 0.000, which is below the threshold of 0.05. This indicates a statistically significant impact of the giant snakes and ladders game on the cognitive development of children aged 5 to 6 years at Cut Nyak Dhien Kindergarten in Malang City. Conclusion : Hence, the giant snakes and ladders educational game has been shown to be an effective pedagogical medium for promoting and enhancing cognitive development among early childhood learners.